Anti-freezing asphalt admixture and asphalt concrete
By growing TiO2 composites in situ on the polyurethane surface and grafting them on carbon fibers to form anti-freeze blends, the problem of asphalt pavement prone to cracking in cold environments is solved, significantly improving the freezing and deformation resistance of asphalt concrete, and extending the service life of the pavement.
Patent Information
- Application Number
- CN202411888595.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-25
AI Technical Summary
In cold and low-temperature environments, asphalt pavement is prone to cracking, which leads to severe challenges in the transportation industry, and the existing technology is difficult to effectively improve the freezing resistance of asphalt mixtures.
By growing the TiO2 composite in situ on the polyurethane surface and grafting it on carbon fibers, an anti-freeze blend is formed, and the microstructure of asphalt concrete is improved and its anti-freeze effect is enhanced.
It significantly improves the freezing effect and deformation resistance of asphalt concrete, reduces the pavement temperature, extends the service life of the pavement, and effectively prevents cracking or damage caused by freezing.
Smart Images

Figure BDA0005200003560000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of asphalt materials, and in particular relates to an antifreeze asphalt admixture and asphalt concrete. Background Art
[0002] Asphalt pavement is the preferred pavement type for highway construction in my country. It is not only widely used in key transportation areas such as airport runways, bridge deck paving, highways and urban roads, but also occupies an overwhelming majority of pavement projects under construction due to its high driving comfort, seamless connection and convenient maintenance characteristics. However, in a cold and low-temperature environment, the viscosity of asphalt increases significantly, its brittleness increases, and its elastic recovery ability also decreases significantly, which makes the road surface more prone to cracking. This problem poses a severe challenge to the development of the transportation industry and brings many troubles and inconveniences to people's daily life and production activities. Therefore, it is urgent to take practical and effective measures to ensure that roads are unobstructed under freezing conditions in winter, ensure driving safety, and thereby reduce or even avoid traffic accidents.
[0003] Chinese patent application CN113185192A discloses an antifreeze asphalt mixture and a preparation method thereof, wherein the antifreeze agent is ultrasonically pretreated to fully mix the rubber powder and the emulsified asphalt powder in the antifreeze agent, thereby improving the dispersibility of the antifreeze agent, thereby making the antifreeze agent more evenly dispersed in the modified asphalt, thereby improving the antifreeze performance of the asphalt mixture. However, the antifreeze agent cannot be evenly dispersed in the modified asphalt only through ultrasonic dispersion, and thus the antifreeze effect cannot be effectively exerted. Summary of the invention
[0004] The purpose of the present invention is to obtain a terminal hydroxyl polyurethane TiO2 complex by in-situ growth of TiO2 on a covalent organic skeleton and grafting it on the surface of polyurethane, and then surface treating carbon fiber with nitric acid or the like to generate a large number of hydroxyl functional groups. Under the action of polyacryl chloride, the terminal hydroxyl polyurethane TiO2 complex is covalently bonded to the surface of carbon fiber. Because of its low thermal conductivity, the movement of polyurethane molecular chains is restricted in a cold environment, but a certain flexibility can be maintained, and the heat loss of asphalt concrete can be reduced, and the heat transfer can be prevented. In addition, the carbon fiber improves the microstructure of asphalt concrete, making it more uniform and dense, and reducing the space for water penetration and ice expansion. The polyurethane has adhesion, which effectively improves the dispersibility and bonding degree of carbon fiber in asphalt concrete, thereby significantly increasing the antifreeze effect of asphalt concrete.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] An asphalt concrete using an antifreeze asphalt admixture is prepared by the following steps:
[0007] Add antifreeze asphalt admixture, waste asphalt particles, limestone crushed stone particles, waste tire particles, coal slag powder and calcium carbonate powder into a reactor, stir for 1-2 hours at 160-180°C and 800-1000r / min, and cool naturally to obtain asphalt concrete.
[0008] Furthermore, the usage ratio of antifreeze asphalt admixture, waste asphalt particles, limestone crushed stone particles, waste tire particles, coal slag powder and calcium carbonate powder is 70-80kg: 40-45kg: 5-6kg: 5-6kg: 4-5kg: 4-5kg.
[0009] The antifreeze asphalt admixture is prepared by the following steps:
[0010] Step 1: Add tetrakis(4-formylphenyl)ethylene, 2,5-diaminobenzoic acid and deionized water into a reactor, stir for 10-15 min at 20-25°C and 500-700 r / min, add dimethylacetamide, N,N-dimethylformamide and 4-5 mol / L acetic acid solution into the reactor, heat to 110-120°C and continue stirring for 1-2h, then add tetrabutyl titanate, continue reacting for 1-2h, filter, wash the filter cake with deionized water and anhydrous ethanol for 2-3 times respectively, and dry under vacuum at 60-80°C for 1-2h to obtain TiO2 composite powder.
[0011] Step 2: add isocyanate, polyether polyol, deionized water and 0.3-0.5% dibutyltin dilaurate solution into a reactor, stir and react at 70-80°C and 500-600r / min for 20-30min, then add TiO2 composite powder into the reactor, continue stirring and reacting for 1-2h, filter, wash the filter cake with deionized water and anhydrous ethanol for 2-3 times respectively, and vacuum dry at 60-80°C for 1-2h to obtain a hydroxyl-terminated polyurethane TiO2 composite.
[0012] Step 3: Stir the carbon fiber with a length of 15-18 mm and the nitric acid solution with a mass fraction of 30-35% at 115-120° C. and 500-600 r / min for 1-1.2 h, filter, wash the filter cake with deionized water and anhydrous ethanol for 2-3 times respectively until the last washing liquid is neutral to obtain surface modified carbon fiber; add the surface modified carbon fiber and 1,4-dioxane solution into the reactor, under the protection of nitrogen, stir at 20-25° C. and 300-400 r / min for 4-5 h, add the polyacryl chloride solution with a mass fraction of 30-35% and triethylamine into the reactor, stir at 70-80° C. and 300-400 r / min for 48-50 h, filter under reduced pressure, wash the filter cake with tetrahydrofuran for 2-3 times to obtain polyacryl chloride grafted carbon fiber.
[0013] Step 4: Add polyacryl chloride grafted carbon fiber and 1,4-dioxane solution into the reactor, stir at 20-25°C and 300-400r / min for 4-5h, then add terminal hydroxyl polyurethane TiO2 complex and triethylamine into the reactor, stir at 70-80°C and 300-400r / min for 48-50h under the protection of nitrogen, filter under reduced pressure, wash the filter cake with tetrahydrofuran for 2-3 times, and vacuum dry at 60-80°C for 1-2h to obtain an antifreeze admixture.
[0014] Step 5: Add asphalt powder and antifreeze admixture into the reactor, shear for 10-20 minutes at 160-180°C and 800-1000r / min to obtain antifreeze asphalt admixture.
[0015] Furthermore, in step 1, the usage ratio of tetrakis(4-formylphenyl)ethylene, 2,5-diaminobenzoic acid, deionized water, tetrabutyl titanate, dimethylacetamide, N,N-dimethylformamide and acetic acid is 1-2kg: 1-2kg: 2-3L: 2-3kg: 700-800mL: 700-800mL: 800-900mL.
[0016] Furthermore, in step 2, the dosage ratio of isocyanate, polyether polyol, deionized water, dibutyltin dilaurate and TiO2 composite powder is 1-1.2L: 1.5-2L: 2-3L: 300-400mL.
[0017] Furthermore, in step three, the usage ratio of carbon fiber and nitric acid is 1-2kg:2-3L.
[0018] Furthermore, in step three, the usage ratio of the surface modified carbon fiber, 1,4-dioxane solution, polyacryl chloride and triethylamine is 2-3kg:10-15L:4-5L:500-600mL.
[0019] Furthermore, in step 4, the usage ratio of polyacryl chloride grafted carbon fiber, 1,4-dioxane solution, terminal hydroxyl polyurethane TiO2 composite and triethylamine is 2-3kg:10-15L:4-5L:500-600mL.
[0020] Furthermore, in step five, the mass ratio of asphalt powder to antifreeze admixture is 70-80:5-6.
[0021] Beneficial effects of the present invention:
[0022] 1. The antifreeze asphalt admixture prepared by the present invention significantly increases the antifreeze effect of asphalt concrete by uniformly mixing asphalt powder with the antifreeze admixture by swelling it at high temperature, effectively improves the deformation resistance of asphalt concrete, and can reduce the road surface temperature in high temperature weather, thereby extending the service life of the road surface.
[0023] 2. The antifreeze admixture of the present invention generates a covalent organic skeleton of TiO2 in situ on the surface of polyurethane and grafts the polyurethane onto carbon fiber. In a low-temperature environment, the movement of the polyurethane molecular chain is restricted, but a certain flexibility can be maintained. The carbon fiber improves the microstructure of the asphalt concrete, making it more uniform and dense, reducing the space for water penetration and ice expansion, and significantly increasing the antifreeze effect of the asphalt concrete. At the same time, the internal microporous structure and the covalent organic skeleton grown on the surface help to absorb and buffer the stress generated during the freezing process, prevent the material from cracking or being damaged due to freezing, and improve the deformation resistance of the asphalt concrete. The polyurethane has adhesion, and grafting on the carbon fiber can effectively improve the bonding degree between the carbon fiber and waste asphalt, limestone gravel, waste tires, coal slag powder and calcium carbonate, which is beneficial to the recycling of waste.
[0024] 3. The hydroxy-terminated polyurethane TiO2 composite of the present invention has a very high specific surface energy and is extremely unstable. It will quickly agglomerate at high temperatures to form metastable larger particles. The TiO2 is dispersed on the surface of the polyurethane through a covalent organic skeleton, further increasing the mechanical strength and toughness of the polyurethane and effectively improving the dispersibility of the TiO2. Under lighting conditions, TiO2 can reflect a large amount of light, especially ultraviolet light, and effectively reflect sunlight back, reducing the absorption of solar radiation by asphalt, thereby significantly reducing the temperature of the asphalt pavement. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Example 1: An antifreeze asphalt admixture and asphalt concrete are prepared by the following steps:
[0027] S1: Add 1kg of tetrakis(4-formylphenyl)ethylene, 1kg of 2,5-diaminobenzoic acid and 2L of deionized water into a reactor, stir at 20°C and 500r / min for 10min, add 700mL of dimethylacetamide, 700mL of N,N-dimethylformamide and 800mL of 4mol / L acetic acid solution into the reactor, heat to 110°C and continue stirring for 1h, then add 2kg of tetrabutyl titanate, continue the reaction for 1h, filter, wash the filter cake twice with deionized water and anhydrous ethanol respectively, and dry it in vacuo at 60°C for 1h to obtain TiO2 composite powder.
[0028] S2: Add 1L of isocyanate, 1L of polyether polyol, 2L of deionized water and 300mL of 0.3% dibutyltin dilaurate solution into a reactor, stir and react at 70°C and 500r / min for 20min, then add 1kg of TiO2 complex powder into the reactor, continue stirring and reacting for 1h, filter, wash the filter cake twice with deionized water and anhydrous ethanol respectively, and dry in vacuum at 60°C for 1h to obtain a terminal hydroxyl polyurethane TiO2 complex.
[0029] TiO2 has a very high specific surface energy and is extremely unstable. It will quickly agglomerate at high temperatures to form larger metastable particles. The dispersibility of TiO2 can be effectively solved by in-situ generating TiO2 complexes on the polyurethane surface and fixing TiO2 on the polyurethane surface through a covalent organic framework.
[0030] S3: 1 kg of 15 mm long carbon fiber and 2 L of 30% nitric acid solution were stirred at 115°C and 500 r / min for 1 h, filtered, and the filter cake was washed twice with deionized water and anhydrous ethanol respectively until the last washing liquid was neutral to obtain surface-modified carbon fiber; 2 kg of surface-modified carbon fiber and 10 L of 1,4-dioxane solution were added to a reactor, stirred at 20°C and 300 r / min for 4 h under the protection of nitrogen, 4 L of 30% polyacryl chloride solution and 500 mL of triethylamine were added to the reactor, stirred at 70°C and 300 r / min for 48 h, filtered under reduced pressure, and the filter cake was washed twice with tetrahydrofuran to obtain polyacryl chloride grafted carbon fiber;
[0031] Polyacryl chloride grafted carbon fiber and 10L 1,4-dioxane solution were added into the reactor, stirred at 20°C and 300r / min for 4h, then 2kg hydroxyl-terminated polyurethane TiO2 complex and 500mL triethylamine were added into the reactor, stirred at 70°C and 300r / min for 48h under the protection of nitrogen, filtered under reduced pressure, washed the filter cake twice with tetrahydrofuran, and dried in vacuum at 60°C for 1h to obtain the antifreeze admixture.
[0032] S4: Add 70 kg of asphalt powder and 5 kg of antifreeze admixture into the reactor, and shear for 10 minutes at 160°C and 800 r / min to obtain the antifreeze asphalt admixture.
[0033] The carbon fiber is surface treated with nitric acid and the like to generate a large number of hydroxyl groups. Polyacryloyl chloride undergoes esterification reaction with the hydroxyl groups through the acyl chloride groups and is grafted onto the surface of the carbon fiber. The active acyl chloride groups of the polyacryloyl chloride grafted onto the surface of the carbon fiber are then reacted with the terminal hydroxyl groups of the polyurethane to covalently graft the polyurethane onto the surface of the carbon fiber.
[0034] Carbon fiber can enhance the tensile strength and other mechanical properties of asphalt concrete, making it stronger and more durable, effectively improving the deformation resistance of asphalt concrete and improving the performance of road surface. However, when added directly as filler, it cannot be evenly dispersed in asphalt concrete and is easy to cluster, affecting the porosity and overall performance of asphalt concrete. The carbon fiber is grafted by end-hydroxy polyurethane TiO2 composite, which has strong adhesion and adsorption, and can help enhance the dispersion and bonding of carbon fiber in asphalt concrete.
[0035] S5: Add 70kg of asphalt powder and 5kg of antifreeze admixture into the reactor, shear for 10min at 160℃ and 800r / min to obtain antifreeze asphalt admixture; add 70kg of antifreeze asphalt admixture, 40kg of waste asphalt particles, 5kg of limestone gravel particles, 5kg of waste tire particles, 4kg of coal slag powder and 4kg of calcium carbonate powder into the reactor, stir for 1h at 160℃ and 800r / min, cool naturally to obtain asphalt concrete.
[0036] Example 2: An antifreeze asphalt admixture and asphalt concrete are prepared by the following steps:
[0037] S1: Add 1.5 kg of tetrakis(4-formylphenyl)ethylene, 1.5 kg of 2,5-diaminobenzoic acid and 2.5 L of deionized water into a reactor, stir for 13 min at 22 °C and 600 r / min, add 750 mL of dimethylacetamide, 750 mL of N,N-dimethylformamide and 850 mL of 4.5 mol / L acetic acid solution into the reactor, heat to 115 °C and continue stirring for 1.5 h, then add 2.5 kg of tetrabutyl titanate, continue the reaction for 1.5 h, filter, wash the filter cake with deionized water and anhydrous ethanol for 3 times respectively, and dry it in vacuo at 70 °C for 1.5 h to obtain TiO2 composite powder.
[0038] S2: 1.1L of isocyanate, 1.7L of polyether polyol, 2.5L of deionized water and 350mL of 0.4% dibutyltin dilaurate solution were added into the reactor, stirred and reacted at 75°C and 550r / min for 25min, then 1.1kg of TiO2 composite powder was added into the reactor, stirred and reacted for 1.5h, filtered, and the filter cake was washed with deionized water and anhydrous ethanol for 3 times respectively, and vacuum dried at 70°C for 1.5h to obtain a hydroxyl-terminated polyurethane TiO2 composite.
[0039] S3: 1.5 kg of 17 mm long carbon fiber and 2.5 L of 33% nitric acid solution were stirred at 118 ° C and 550 r / min for 1.1 h, filtered, and the filter cake was washed with deionized water and anhydrous ethanol for 3 times respectively until the last washing liquid was neutral to obtain surface-modified carbon fiber; 2.5 kg of surface-modified carbon fiber and 12 L of 1,4-dioxane solution were added to the reactor, stirred at 22 ° C and 350 r / min for 4.5 h under the protection of nitrogen, 4.5 L of 33% polyacryl chloride solution and 550 mL of triethylamine were added to the reactor, stirred at 78 ° C and 350 r / min for 49 h, filtered under reduced pressure, and the filter cake was washed with tetrahydrofuran for 3 times to obtain polyacryl chloride grafted carbon fiber;
[0040] Polyacryloyl chloride grafted carbon fiber and 12L 1,4-dioxane solution were added into the reactor, stirred at 22°C and 350r / min for 4.5h, then 2.5kg hydroxyl-terminated polyurethane TiO2 complex and 550mL triethylamine were added into the reactor, stirred at 78°C and 350r / min for 49h under the protection of nitrogen, filtered under reduced pressure, washed the filter cake with tetrahydrofuran for 3 times, and dried in vacuum at 70°C for 1.5h to obtain the antifreeze admixture.
[0041] S4: Add 75 kg of asphalt powder and 5.5 kg of antifreeze admixture into the reactor, and shear for 11 minutes at 170°C and 900 r / min to obtain the antifreeze asphalt admixture.
[0042] S5: Add 75kg of asphalt powder and 5.5kg of antifreeze admixture into the reactor, shear for 15min at 170℃ and 900r / min to obtain antifreeze asphalt admixture; add 78kg of antifreeze asphalt admixture, 43kg of waste asphalt granules, 5.5kg of limestone gravel granules, 5.5kg of waste tire granules, 4.5kg of coal slag powder and 4.5kg of calcium carbonate powder into the reactor, stir for 1.5h at 170℃ and 900r / min, cool naturally to obtain asphalt concrete.
[0043] Example 3: An antifreeze asphalt admixture and asphalt concrete are prepared by the following steps:
[0044] S1: Add 2kg of tetrakis(4-formylphenyl)ethylene, 2kg of 2,5-diaminobenzoic acid and 3L of deionized water into a reactor, stir for 15min at 25°C and 700r / min, add 800mL of dimethylacetamide, 800mL of N,N-dimethylformamide and 900mL of 5mol / L acetic acid solution into the reactor, heat to 120°C and continue stirring for 2h, then add 3kg of tetrabutyl titanate, continue the reaction for 2h, filter, wash the filter cake with deionized water and anhydrous ethanol for 3 times respectively, and dry it in vacuo at 80°C for 2h to obtain TiO2 composite powder.
[0045] S2: Add 1.2L of isocyanate, 2L of polyether polyol, 3L of deionized water and 400mL of 0.5% dibutyltin dilaurate solution into a reactor, stir and react at 80°C and 600r / min for 30min, then add 1.2kg of TiO2 complex powder into the reactor, continue stirring and react for 2h, filter, wash the filter cake with deionized water and anhydrous ethanol for 3 times respectively, and dry in vacuum at 80°C for 2h to obtain a hydroxyl-terminated polyurethane TiO2 complex.
[0046] S3: 2 kg of 18 mm long carbon fiber and 3 L of 35% nitric acid solution were stirred at 120 ° C and 600 r / min for 1.2 h, filtered, and the filter cake was washed with deionized water and anhydrous ethanol for 3 times respectively until the last washing liquid was neutral to obtain surface-modified carbon fiber; 3 kg of surface-modified carbon fiber and 15 L of 1,4-dioxane solution were added to the reactor, stirred at 25 ° C and 400 r / min for 5 h under the protection of nitrogen, 5 L of 35% polyacryl chloride solution and 600 mL of triethylamine were added to the reactor, stirred at 80 ° C and 400 r / min for 50 h, filtered under reduced pressure, and the filter cake was washed with tetrahydrofuran for 3 times to obtain polyacryl chloride grafted carbon fiber;
[0047] Polyacryl chloride grafted carbon fiber and 15L 1,4-dioxane solution were added into the reactor, stirred at 25°C and 400r / min for 5h, then 3kg hydroxyl-terminated polyurethane TiO2 composite and 600mL triethylamine were added into the reactor, stirred at 80°C and 400r / min for 50h under the protection of nitrogen, filtered under reduced pressure, washed the filter cake with tetrahydrofuran for 3 times, and dried in vacuum at 80°C for 2h to obtain the antifreeze admixture.
[0048] S4: 80 kg of asphalt powder and 6 kg of antifreeze admixture are added into a reactor, and sheared for 12 min at 180°C and 1000 r / min to obtain antifreeze asphalt admixture.
[0049] S5: Add 80kg of asphalt powder and 6kg of antifreeze admixture into the reactor, shear for 20min at 180℃ and 1000r / min to obtain antifreeze asphalt admixture; add 80kg of antifreeze asphalt admixture, 45kg of waste asphalt particles, 6kg of limestone gravel particles, 6kg of waste tire particles, 5kg of coal slag powder and 5kg of calcium carbonate powder into the reactor, stir for 2h at 180℃ and 1000r / min, cool naturally to obtain asphalt concrete.
[0050] Comparative Example 1: Based on Example 3, the terminal hydroxyl polyurethane TiO2 composite and carbon fiber in step S3 are stirred and mixed, ultrasonically dispersed, and the remaining steps remain unchanged to prepare asphalt concrete.
[0051] Comparative Example 2: Based on Example 3, the TiO2 composite powder in step S2 was replaced with commercially available TiO2 powder, and the remaining steps remained unchanged to prepare asphalt concrete.
[0052] Comparative Example 3: Based on Example 3, asphalt concrete was prepared according to the method of step S1 without adding tetrabutyl titanate and keeping the other steps unchanged.
[0053] In the embodiments and comparative examples:
[0054] Tetrakis(4-formylphenyl)ethylene, 2,5-diaminobenzoic acid, dimethylacetamide, N,N-dimethylformamide, acetic acid, tetrabutyl titanate, isocyanate, 1,4-dioxane solution, triethylamine and polyacryloyl chloride were all purchased from Sigma-Aldrich.
[0055] Polyether polyols were purchased from Nantong Zimeng Chemical Co., Ltd.
[0056] Carbon fiber was purchased from Shanghai Hanma Construction Technology Co., Ltd.
[0057] Asphalt powder was purchased from Hebei Fengtaiyuan Energy Technology Co., Ltd.
[0058] Limestone crushed stone particles were purchased from Wulian County Mengze Stone Co., Ltd.
[0059] Waste tire particles were purchased from Guangzhou Huaxiu Plastic Co., Ltd.
[0060] Cinder powder and calcium carbonate powder were purchased from Changsha Danuo Building Materials Co., Ltd.
[0061] The asphalt concrete prepared in Example 1 to Example 3 and Comparative Example 1 to Comparative Example 3 was tested for performance, and the results are shown in Table 1:
[0062] 1. High temperature deformation resistance: Refer to the high temperature stability test in the standard "Technical Specifications for Highway Asphalt Pavement Construction" (JTGF40-2004) to test the deformation resistance under high temperature conditions. The high temperature performance test temperature is 50°C. The results are expressed by the maximum stress when the asphalt concrete is damaged - Marshall stability (kN). The greater the stability, the stronger the deformation resistance.
[0063] 2. Loss of compressive strength: Take a cubic box of 15cm×15cm×15cm, pour asphalt concrete into the cubic box, stop adding when the height reaches 13cm, then add deionized water to fill the cubic box, put it in a -20℃ low temperature box and freeze it for 6h, take it out and then bathe it in a 60℃ constant temperature stirring circulating water bath for 4h, this is to complete a freeze-thaw cycle, the number of freeze-thaw cycles is 8 times, 12 times and 16 times, after all cycles are completed, soak all samples in 20℃ water for 2h, wipe off the surface moisture and then test the compressive performance: refer to (T0713-2000) in the "Test Procedure for Asphalt and Asphalt Mixture in Highway Engineering" (JTJ052-2000) for detection.
[0064] 3. Temperature test: refer to the standard "Hot Mix Asphalt Mixture Construction Temperature Test Method" (T0981-2008); take a 15cm×15cm×15cm cubic box, pour the asphalt concrete of different components into the cubic box respectively, wait for it to solidify, place it in the outdoor sunlight at an outdoor temperature of 20°C, with a light intensity of 50,000 lux and an exposure time of 5 hours, and use an infrared thermometer to measure the temperature of the asphalt concrete of different components.
[0065] Table 1
[0066]
[0067] It can be seen from Table 1 that the deformation resistance and frost resistance of Examples 1 to 3 are significantly better than those of Comparative Examples 1-2, and the temperature reduction capability is significantly better than that of Comparative Example 3. By in-situ generating a covalent organic skeleton of TiO2 on the surface of polyurethane and grafting polyurethane onto carbon fiber, the deformation resistance and frost resistance of asphalt concrete can be significantly increased. TiO2 has a very high specific surface energy and is extremely unstable. It will quickly agglomerate at high temperatures. Through the covalent organic skeleton, TiO2 is dispersed on the surface of polyurethane, which further increases the mechanical strength and toughness of polyurethane and effectively improves the dispersibility of TiO2, thereby significantly reducing the temperature of the asphalt pavement.
[0068] In Comparative Example 1, the terminal hydroxyl polyurethane TiO2 composite and carbon fiber are stirred and evenly mixed, and ultrasonically dispersed, so that the terminal hydroxyl polyurethane TiO2 composite cannot be tightly combined with the carbon fiber, thereby reducing the stability, weakening the deformation resistance of the asphalt concrete, increasing the loss of compressive strength, and weakening the frost resistance; in Comparative Example 2, the TiO2 composite powder is replaced with commercially available TiO2 powder, and the TiO2 is directly dispersed on the surface of the polyurethane by physical adsorption, without forming a covalent organic skeleton, thereby affecting the deformation resistance and frost resistance of the asphalt concrete; in Comparative Example 3, tetrabutyl titanate is not added, but a covalent organic skeleton is loaded on the surface of the polyurethane and grafted onto the carbon fiber, which can still increase the stability of the asphalt concrete and reduce the loss of compressive strength, enhance the deformation resistance and frost resistance of the asphalt concrete, so there is no significant difference from Example 3, but without the addition of tetrabutyl titanate, TiO2 cannot be generated and the temperature of the asphalt pavement cannot be reduced.
[0069] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0070] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. An antifreeze asphalt admixture, characterized in that: Prepared by the following steps: Step 1: Add the surface modified carbon fiber and 1,4-dioxane solution into a reactor, stir at 20-25°C and 300-400r / min for 4-5h under the protection of nitrogen, add 30-35wt% polyacryl chloride solution and triethylamine into the reactor, stir at 70-80°C and 300-400r / min for 48-50h, filter under reduced pressure, wash the filter cake with tetrahydrofuran 2-3 times, and obtain polyacryl chloride grafted carbon fiber; Step 2: Add polyacryloyl chloride grafted carbon fiber and 1,4-dioxane solution into a reaction kettle, stir at 20-25°C and 300-400r / min for 4-5h, then add hydroxyl-terminated polyurethane TiO2 complex and triethylamine into the reaction kettle, stir at 70-80°C and 300-400r / min for 48-50h under the protection of nitrogen, filter under reduced pressure, wash the filter cake with tetrahydrofuran for 2-3 times, and vacuum dry at 60-80°C for 1-2h to obtain an antifreeze admixture; Step 3: Add asphalt powder and antifreeze admixture into the reactor, shear for 10-20 minutes at 160-180°C and 800-1000r / min to obtain antifreeze asphalt admixture.
2. The antifreeze asphalt admixture according to claim 1, characterized in that: The surface modified carbon fiber described in step 1 is prepared by the following steps: A carbon fiber having a length of 15-18 mm and a 30-35 wt% nitric acid solution are stirred at 115-120° C. and 500-600 r / min for 1-1.2 h, filtered, and the filter cake is washed with deionized water and anhydrous ethanol for 2-3 times respectively until the last washing liquid is neutral, thereby obtaining a surface-modified carbon fiber; The usage ratio of the carbon fiber and nitric acid is 1-2kg:2-3L.
3. The antifreeze asphalt admixture according to claim 1, characterized in that: The hydroxyl-terminated polyurethane TiO2 composite described in step 2 is prepared by the following steps: Add isocyanate, polyether polyol, deionized water and 0.3-0.5% dibutyltin dilaurate solution into a reactor, stir and react at 70-80°C and 500-600r / min for 20-30min, then add TiO2 composite powder into the reactor, continue stirring for 1-2h, filter, wash the filter cake with deionized water and anhydrous ethanol for 2-3 times respectively, and vacuum dry at 60-80°C for 1-2h to obtain a hydroxyl-terminated polyurethane TiO2 composite.
4. The antifreeze asphalt admixture according to claim 3, characterized in that: The TiO2 composite powder is prepared by the following steps: Add tetrakis(4-formylphenyl)ethylene, 2,5-diaminobenzoic acid and deionized water into a reaction kettle, stir at 20-25°C and 500-700r / min for 10-15min, add dimethylacetamide, N,N-dimethylformamide and 4-5mol / L acetic acid solution into the reaction kettle, heat to 110-120°C and continue stirring for 1-2h, then add tetrabutyl titanate, continue reacting for 1-2h, filter, wash the filter cake with deionized water and anhydrous ethanol for 2-3 times respectively, and dry under vacuum at 60-80°C for 1-2h to obtain TiO2 composite powder.
5. The antifreeze asphalt admixture according to claim 3, characterized in that: The dosage ratio of the isocyanate, the polyether polyol, the deionized water, the dibutyltin dilaurate and the TiO2 composite powder is 1-1.2L: 1.5-2L: 2-3L: 300-400mL.
6. The antifreeze asphalt admixture according to claim 4, characterized in that: The usage ratio of tetrakis(4-formylphenyl)ethylene, 2,5-diaminobenzoic acid, deionized water, tetrabutyl titanate, dimethylacetamide, N,N-dimethylformamide and acetic acid is 1-2kg: 1-2kg: 2-3L: 2-3kg: 700-800mL: 700-800mL: 800-900mL.
7. The antifreeze asphalt admixture according to claim 1, characterized in that: The usage ratio of the surface modified carbon fiber, 1,4-dioxane solution, polyacryl chloride and triethylamine in step 1 is 2-3kg: 10-15L: 4-5L: 500-600mL.
8. The antifreeze asphalt admixture according to claim 1, characterized in that: In step 1, the usage ratio of the polyacryl chloride grafted carbon fiber, 1,4-dioxane solution, hydroxyl-terminated polyurethane TiO2 composite and triethylamine is 2-3kg: 10-15L: 4-5L: 500-600mL.
9. The antifreeze asphalt admixture according to claim 1, characterized in that: The mass ratio of the asphalt powder and the antifreeze admixture in step three is 70-80:5-6.
10. An asphalt concrete, characterized in that: The raw materials include the antifreeze asphalt admixture described in claim 1, and the asphalt concrete is prepared by the following steps: Add 70-80kg of antifreeze asphalt admixture, 40-45kg of waste asphalt particles, 5-6kg of limestone crushed stone particles, 5-6kg of waste tire particles, 4-5kg of coal slag powder and 4-5kg of calcium carbonate powder into the reactor, heat to 160-180℃, stir at a speed of 800-1000r / min for 1-2h, cool naturally to obtain asphalt concrete.
Citation Information
Patent Citations
Anti-freezing asphalt mixture and preparation method thereof
CN113185192A